COMPARING DIAGNOSTIC ACCURACY OF GENE XPERT IN STOOL VERSUS GASTRIC ASPIRATION CHILDREN WITH TUBERCULOSIS (The Research of Medical Science Review, 2025)
Background: Tuberculosis (TB) remains a leading cause of pediatric mortality, with 1.1 million new childhood cases annually. Diagnosis is challenging due to nonspecific symptoms and difficulties in obtaining respiratory samples. While gastric aspirate GeneXpert offers high accuracy, its invasiveness limits use in resource-limited settings. The WHO now endorses stool-based GeneXpert as a non-invasive alternative, but comparative data in children are scarce. Objective: This study compared the diagnostic accuracy of stool versus gastric aspirate GeneXpert for pediatric pulmonary TB in a high-burden setting. Methodology: A cross-sectional study enrolled 187 children (aged 2–12 years) with suspected TB at a tertiary hospital in Pakistan. Stool and gastric aspirate samples were tested using GeneXpert, with gastric aspirate culture as the gold standard. Sensitivity, specificity, predictive values, and ROC curves were calculated. Results: Stool GeneXpert showed 63% sensitivity (38/60 true positives) and 76.7% specificity (97/127 true negatives), with 72.2% accuracy. Gastric aspirate GeneXpert demonstrated superior performance: 86% sensitivity (52/60 true positives), 92% specificity (117/127 true negatives), and 89.8% accuracy. Positive predictive values were 55.9% (stool) versus 83.9% (gastric aspirate). ROC analysis confirmed higher diagnostic utility for gastric aspirate (AUC=0.89 vs. 0.69 for stool). Clinical symptoms (chronic cough: 82%, fever: 72%, weight loss: 65%) and radiologic findings (74% hilar lymphadenopathy) were prevalent, but diagnostic performance did not vary by age or gender (*p* > 0.05). Conclusion: While gastric aspirate GeneXpert remains the gold standard for pediatric TB diagnosis, stool testing provides a feasible, non-invasive alternative in resource-limited settings. Despite lower sensitivity, stool GeneXpert’s ease of collection supports its WHOrecommended role, particularly where gastric aspirate is impractical. Further optimization of stool-based protocols is needed to improve diagnostic yield.